THE EFFECT OF GAME-BASED LEARNING ON IMPROVEMENT STUDENTS' LEARNING OUTCOMES IN CLASS X CULTURAL ARTS SUBJECT - Mettang, Silva Arruan; Pratama, Muh.Putra; Ervianti, Ervianti (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2024)
This study is a quantitative research employing an experimental approach. The aim is to determine the impact of game-based learning on improving student learning outcomes in class X Cultural Arts subjects at SMA Negeri 6 North Toraja. The type of experimental research used is quasi-experimental with a pretest-posttest control group design. Data was collected through observation and a test consisting of 20 valid questions, with the help of SPSS 29 for data analysis. The population of this study includes all class X students at SMA Negeri 6 North Toraja, totaling 91 students. The sample comprises two classes: class X2 as the control group and class X3 as the experimental group. The statistical test results, based on post-test data from both classes, revealed that the post-test scores of the experimental and control groups were normally distributed. The independent samples t-test indicated a statistically significant difference in the average learning outcomes between the experimental and control groups, with a significance value (2-tailed) of 0.01, which is less than 0.05. Therefore, H0 (null hypothesis) is rejected, and H1 (alternative hypothesis) is accepted. In conclusion, game-based learning significantly affects student learning outcomes in the Cultural Arts subject for class X at SMA Negeri 6 North Toraja.